ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KONSUMEN MILLENIAL DALAM KEPUTUSAN PEMBELIAN HP VIVO DI BANGKINANG KOTA - Nurliana Nurliana; Samsurijal Hasan (STIE Bangkinang Publishing, 2020)
This study aims to determine the factors that influence Millennial consumers in purchasing decisions for Vivo HP in Bangkinang City. The population in this study are buyers belonging to the millennial age range of 15-34 years. The sample is determined by the Porposive Sampling method with the number of respondents in this study as many as 100 people with multiple linear regression analysis. The type of data used consists of primary and secondary data. The data is collected using a questionnaire and research file. From the results of the validity test, all items of the statement submitted to the respondent were declared valid with a calculated value greater than the rtable value (0.197). The reliability test results also showed that each item had a good level of reliability with Cronbach's alpha values ​​above 0.5. From the results of the study it can be concluded that the independent variables namely culture, social and personal simultaneously influence the purchasing decisions of Vivo HP in Bangkinang City, while partially cultural, social and probability variables influence the purchasing decisions of Vivo HP in Bangkinang City where the significance is 0,000 for cultural variables, 0.001 for social variables, and 0.036 for personal variables where < 0,05. The multiple correlation coefficient (R) value of 0.804 means that the relationship between the independent variable and the dependent variable is classified as strong with a coefficient of determination (R2) of 64.7%.